Queer nuns: religion, activism, and serious parody - Wilcox, Melissa M. (Sexual cultures, 2018)
"Modern-day badass drag queen superhero nuns" -- "It was like this asteroid belt": the origins and growth of the sisters -- "We are nuns, silly!": serious parody as activism -- "A sacred, powerful woman": complicating gender -- "Sister outsiders": navigating whiteness -- "A secular nun": serious parody and the sacred -- New world order? -- Blooper reel -- Studying the sisters